Abuse of Authority in Modern Automotive Workshop Employment Relationships: An Analysis of Embezzlement in Office in Specialized Car Air Conditioning and Suspension Workshops - Albertin, Thomas; Panggabean, Mompang L; Siregar, Rospita Adelina (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Embezzlement in office constitutes a form of crime arising from the abuse of trust within employment relationships, particularly in the automotive workshop sector, which is characterized by intensive asset management and high-frequency daily transactions. Modern car workshops operate through complex interactions involving cash handling, spare parts circulation, and technical service authority, creating structural vulnerabilities to occupational crime.Purposes of the Research: This article aims to analyze the practice of embezzlement in office within specialized car air conditioning and suspension workshops, with particular emphasis on the legal construction of employment relationships, the scope of employee authority, and the lawful possession of property that is subsequently abused.Methods of the Research: The research employs a statutory and conceptual approach, focusing primarily on the provisions of Article 488 of the New Indonesian Criminal Code. Doctrinal analysis is used to examine the elements of the offense, especially in relation to authority, trust, and asset control within the framework of employment.Findings of the Research: The analysis demonstrates that the operational characteristics of automotive workshops—such as cash management, spare parts administration, administrative record-keeping, and delegated technical service authority—generate heightened susceptibility to embezzlement aggravated by position. The article asserts that the elements of an “employment relationship” and “trust” constitute decisive factors in establishing embezzlement in office, thereby distinguishing it from ordinary embezzlement. This research underscores the necessity of a comprehensive understanding of employment relations and mechanisms of asset possession to ensure the accurate and proportional application of criminal law.